Microarray and quantitative PCR analysis of gene expression profiles in response to treatment with tomato leaf extract in MCF-7 breast cancer cells - Amid, Azura; Wan Chik, Wan Dalila; Jamal, Parveen; Hashim, Yumi Zuhanis Has-Yun (National Cancer Center, Korea., 2013)
We previously found cytotoxic effects of tomato leaf extract (TLE) on the MCF-7 breast cancer cell line. The aim of this study was to ascertain the molecular mechanisms associated with the usage of TLE as an anticancer agent by microarray analysis using mRNA from MCF-7 breast cancer cells after treatment with TLE for 1 hr and 48 hrs. Approximately 991 genes out of the 30,000 genes in the human genome were significantly (p<0.05) changed after the treatment. Within this gene set, 88 were significantly changed between the TLE treated cells and the untreated MCF-7 cells (control cells) with a cut-off fold change >2.00. In order to focus on genes that were involved in cancer cell growth, only twenty-nine genes were selected, either down-regulated or up-regulated after treatment with TLE. Microarray assay results were confirmed by analyzing 10 of the most up and down regulated genes related to cancer cells progression using real-time PCR. Treatment with TLE induced significant up-regulation in the expression of the CRYAB, PIM1, BTG1, CYR61, HIF1-α and CEBP-β genes after 1 hr and 48 hrs, whereas the TXNIP and THBS1 genes were up-regulated after 1 hr of treatment but down-regulated after 48 hrs. In addition both the HMG1L1 and HIST2H3D genes were down-regulated after 1 hr and 48 hrs of treatment. These results demonstrate the potent activity of TLE as an anticancer agent.